Collective Bargaining in the Public Services of Canada - Anderson, John c.; Kochan, Thomas A. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1977)
This paper examines the existing System of collective bargaining in the Public Service of Canada and the legislative suggestions of the Parliamentary Committee on Employer-employee Relations in the Public Service in light of the results of two major empirical investigations of collective bargaining in the federal public service of Canada.